2018
DOI: 10.1113/jp277036
|View full text |Cite
|
Sign up to set email alerts
|

Lamina‐specific population encoding of cutaneous signals in the spinal dorsal horn using multi‐electrode arrays

Abstract: Key points Traditional, widely used in vivo electrophysiological techniques for the investigation of spinal processing of somatosensory information fail to account for the diverse functions of each lamina.To overcome this oversimplification, we have used multi‐electrode arrays, in vivo, to simultaneously record neuronal activity across all laminae of the spinal dorsal horn.Multi‐electrode arrays are sensitive enough to detect lamina‐ and region‐specific encoding of different subtypes of afferent fibres and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Many in vivo electrophysiologists are now using electrodes with multiple contacts to record from more than one neuron during a protocol, with a single probe containing 384 recording channels (Jun et al, 2017) or being inserted into multiple lamina within the spinal cord (Greenspon et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Many in vivo electrophysiologists are now using electrodes with multiple contacts to record from more than one neuron during a protocol, with a single probe containing 384 recording channels (Jun et al, 2017) or being inserted into multiple lamina within the spinal cord (Greenspon et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The final window timings for each stimulation paradigm are displayed in table 1. Previous studies have reported a sustained elevated response to thermal stimulation after cessation of the stimulus [50,51]; we therefore also analysed a second window for noxious thermal responses from the end of the stimulus response window (1.5 s post-stimulus onset) to the end of our recording block (4.5 s post-stimulus onset). For this condition, as we did not have 3 s of pre-stimulus data, a 1 s pre-stimulus window was used and spike counts were multiplied by 3.…”
Section: Spike-sorting and Cell Classificationmentioning
confidence: 99%
“…A feedback-controlled heating blanket (ALC-HTP, Shanghai Alcott Biotech Co., People's Republic of China) was used to monitor and maintain core body temperature at 37.0 ± 0.5°C. 22 Extracellular Recording of the SDH Neurons Extracellular recording of SDH neurons was performed at L4-6 segments through a 5 MΩ parylene-coated tungsten microelectrode 23 (575,500, A-M Systems, Sequim, WA, United States) or a microelectrode array 24 (ASSY, Lotus Biochips, United States) (Figure 1A and B). After surgery, recording electrodes were inserted perpendicularly into the SDH at a depth of approximately 600-1400 μm from the dorsal surface and 0.3 mm lateral to the central vessel by a micromanipulator (DMA-1510, Narishige, Japan).…”
Section: Perfusion and Tissue Processingmentioning
confidence: 99%